THE INFLUENCE OF EARNING ZAKAT DISTRIBUTION LEVEL ON ZAKAT MUSTAHIK BUSINESS PROFIT - Ahmad Agung; Yati Hilmi; Asri Awaliyah Fitri (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Darussalam (IAID) Ciamis, Jawa Barat, INDONESIA, 2021)
This research is motivated by the administration that has not been well organized and the absence of training for BMT and mustahik recipients of productive zakat funds by the National Amil Zakat Agency (BAZNAS) Ciamis Regency. Quantitative field research using a simple linear regression method uses a sample of 30 people. The results showed that (1) Most respondents agreed that the utilization of productive zakat funds at BAZNAS Ciamis Regency through BMT-BMT in Cijeunjing District was quite good. (2) Most respondents agree that the empowerment of mustahik at BAZNAS in Ciamis Regency through BMT-BMT in Cijeunjing District is quite good. (3) The variable utilization of productive zakat funds (X) does not affect the empowerment of mustahik (Y) BAZNAS Ciamis Regency through BMT-BMT in Cijeunjing District.